Conservation management practices reduce non-point source pollution from grazed pastures. Issue 2 (February 2021) - Ashworth, Amanda J.; Moore, Philip A.; Pote, Dan H.; Owens, Phillip R.; Martin, Jerry W.; Anderson, Kelsey R.
Abstract: Producers in Northwest Arkansas and globally need alternative management practices to ensure long-term sustainable and economical use of poultry litter, which is an abundant source of valuable carbon (C), nitrogen (N) and phosphorus (P). Project objectives were to measure the efficacy of conservation management practices (i.e., pasture aeration and subsurface litter incorporation) to reduce nutrient runoff compared to poultry litter surface applications from small watersheds under rainfed and grazed conditions. Watersheds (0.23 ha each) were assigned a treatment [pasture aeration, subsurface litter incorporation, or surface application of litter (positive control)] on a Leadvale (fine-silty, siliceous, thermic Typic Fragiudult) silt loam. Poultry litter was applied annually to each watershed from 2007-2012. Over the 4-yr study period, runoff loads of NO3 –N, total nitrogen (TN), soluble reactive phosphorus (SRP), and total phosphorus (TP) varied per conservation practice ( P ≤ 0.05). Specifically, average annual loads of NO3 –N, TN, SRP, and TP loads were reduced 49, 42, 28, and 35% following pasture aeration and by 78, 72, 55, and 59% from subsurface applying poultry litter, relative to surface applications, respectively. Greatest annual N loads and runoff corresponded with surface poultry litter applications, followed by pasture aeration, with subsurface incorporation of poultry litter resulting in lowest ( P ≤ 0.05) TN and NO3 –N loads. Overall, subsurface incorporation of poultry litter and pasture aeration are two promising conservation practices for reducing non-point source pollution in watersheds with nutrient imbalances. Further work needs to be done on factors influencing the efficacy of these conservation practices under rainfed conditions, as well as the economic feasibility of these conservation agricultural practices. Abstract : Nutrient loads; Best management practices; Grazing systems; Nitrogen; Phosphorus, Poultry litter.